(untitled) (ENTHYMEMA, 2020)
This article deals with some of the difficulties that arise for the translator when there are no equivalences between the cultures of the languages ​​involved in the translation process. The case of myths is addressed, which may be typical of a culture other than the Arab and which are foreign to the Islam belief system. Certain aspects of this question are explained, since some inconveniences that may arise stem from the characteristics of the terminology of religious discourse.